Terras caídas: riscos e desastres no município e na cidade de São Paulo de Olivença, AM - Rodrigues, Francisco Gleison de Souza (2024)
The state of Amazonas presents a process of human occupation related to the river channels of the main rivers that cross the territory, favoring the emergence of cities that expanded their dimensions without urban planning. This spatial expansion makes residents and urban structures susceptible to the occurrence of erosive events followed by mass movements known regionally as Terras Caídas, which are classified as disasters depending on their magnitude and intensity. In the city of São Paulo de Olivença, on the banks of the Solimões River, there are Terras Caídas in which residential and commercial buildings are lost or damaged. It is proposed that, in the city of São Paulo de Olivença, the occurrences of disasters associated with the Terras Caídas are related to natural processes, arising from characteristics of the geological and pedological structures in the urban settlement area, the morphological and hydraulic dynamics of the river, neotectonics and regional climate, which interact with land use and occupation processes related to disorderly urban expansion in the municipal headquarters and lack of attention to risks. The present research obtained the following results: São Paulo de Olivença presents areas susceptible to the risks and disasters of Terras Caídas, mainly, the relief forms that have facies bordering the Solimões and, in which, part of the population is settled; seven landscape units present in the municipality were delimited and characterized; the facies of the dissected hills and low hills associated with the Solimões Formation in direct contact with the river channel are not suitable for use and occupation due to the high risk of landslides, preventing any type of human activity; in the last forty years there has been a population increase associated with a disorderly urban expansion, which determined the occupation of areas associated with fallen lands promoted by Solimões; in 2010, the occurrence of a Terras Caídas event demonstrated that the inhabitants of the city's edge were in vulnerable conditions in the face of the disaster that occurred; the urban headquarters of the municipality presents another risk, which could consolidate itself as a disaster, causing damage and requiring emergency care: the annual floods of the Solimões River. The city of São Paulo de Olivença finds itself in an environmental and human context that favors the occurrence of disasters related to the Terras Caídas. Aspects such as lithology, relief, climate and soil correlate with the process of occupation of the banks of the Solimões River, generating risk situations and the occurrence of urban disasters.